Emerging Issues in Groundwater Resources - Fares, Ali (Advances in Water Security, 2016)
This book discusses how emerging groundwater risks under current and potential climate change conductions reduce available groundwater resources for domestic use, and agriculture and energy production. The topics discussed throughout this book are grouped into five sections; (i) Sea Level Rise, Climate Change, and Food Security, (ii) Emerging Contaminants, (iii) Technologies and Decision Support Systems, (iv) Surface Water-Groundwater Interactions, and (v) Economics, and Energy Production and Development. This book is unique and different from other groundwater hydrology books in that it uses a holistic approach in investigating the risks related to groundwater resources. This book will be of interest to a wide audience in academia, governmental and non-governmental organizations, and environmental entities. This book will greatly contribute to a better understanding of the emerging risks to groundwater resources and should help responsible stakeholders make informed decisions in this regard. .